SALINITY INDUCED RESPIRATORY ALTERATIONS IN ESTUARINE CLAM PAPHIA LATERISULCA AT BHATYE ESTUARY, RATNAGIRI COAST, INDIA - S. S. TAWARE,; D. V. MULEY, (The Bioscan, 2014)
Present study clearly indicated size as well as season dependant variation in oxygen consumption rate (OCR) in estuarine clam P. laterisulca, exposed to various salinity ranges (100% to 10%). During all three seasons (summer, post-monsoon and winter) smaller clams showed more sensitivity and tolerance undergone lower salinity stress condition than medium and larger size clam. Even, clams of all three sizes respond toward lower salinity ranges in similar fashion, their degree of tolerance and time taken by them to adjust in lower salinity varied with both size and seasons. Overall, all three size clams seasonal metabolic alteration indicates tolerance to 40% reduction in salinity from normal saline water.